1996
DOI: 10.1111/j.1530-0277.1996.tb01043.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Japanese Alcoholics with the Atypical Aldehyde Dehydrogenase 2*2.I. A Comparison of the Genotypes of ALDH2, ADH2, ADH3, and Cytochrome P‐4502E1 Between Alcoholics and Nonalcoholics

Abstract: We examined the genotypes of the aldehyde dehydrogenase (ALDH)-2, alcohol dehydrogenase (ADH)-2, ADH3, and P-4502E1 loci of 53 alcoholics and 97 nonalcoholics. All of the subjects fulfilled the DSM-III-R criteria for alcohol dependence. The control group consisted of 97 subjects who were either hospital staff or students. We also compared the frequencies of homozygous ALDH2*1/1 and heterozygous ALDH2*1/2 genotypes in alcoholics. Our study revealed differences in the allelic frequencies of the ALDH2, ADH2, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
80
2

Year Published

1998
1998
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 112 publications
(89 citation statements)
references
References 22 publications
7
80
2
Order By: Relevance
“…The results of studies of Asian and European populations show that ADH1B*1 predominated among alcohol addicts and suggest a high risk of alcohol addiction (9,(26)(27)(28)(29). Hence, these investigators emphasize the importance of ADH1B*2 protection against developing alcohol dependence (3,24,(30)(31)(32)(33)(34)(35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of studies of Asian and European populations show that ADH1B*1 predominated among alcohol addicts and suggest a high risk of alcohol addiction (9,(26)(27)(28)(29). Hence, these investigators emphasize the importance of ADH1B*2 protection against developing alcohol dependence (3,24,(30)(31)(32)(33)(34)(35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that the ADH1C*1 allele and ADH1C*1/*1 genotype are likely to favor alcohol dependence. Different results were obtained in studies of Asian populations (26)(27)(28), which showed that the ADH1C*1 allele has protective effects against excessive alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%
“…For the ALDH2 polymorphism, all studied individuals but 1 among Mexican Americans 26 in alcoholism and 1 among Caucasians 31 in alcoholic liver disease, were homozygous for the *1/*1 genotype in Caucasians and Americans; therefore, the analysis was restricted to East Asians. [2][3][4]8,11,27,28,32,35,37,[39][40][41][42][43][44]46,56,57 There was heterogeneity among studies (P Ͻ .01), and the allele contrast was highly significant (RE OR ϭ 4.35 [95% CI 3.04, 6.23]). The recessive and dominant models for the effect of allele ALDH2*1 showed highly significant associations.…”
Section: Adh2mentioning
confidence: 99%
“…In studies of alcoholism, the distribution of genotypes in the control group departured from HWE in two studies for ADH2, 41,48 in five studies for ADH3, 5,26,29,31,45 in nine studies for ALDH2, 6,8,26,[29][30][31]47,51,56 and in two studies for CYP2E1. 11,60 Because a lack of HWE indicates possible genotyping errors and/or population stratification, a sensitivity analysis was performed excluding studies not in HWE.…”
Section: Summary Statisticsmentioning
confidence: 99%
See 1 more Smart Citation